Penerapan Aplikasi Location Based Service Dalam Penangganan Gangguan Jaringan Berbasis Mobile - Capah, Dwi Ade Handayani; Herdi, Tazkiyah (Journal of Information System and Informatics, 2021)
Location Based Service is the ability to find the geographic location of a mobile device and provide services based on the location it gets. The development of location base service applications has been widely used today, one part that needs attention to be applied by this application is the handling of network disturbances in service companies. In the field of handling network disturbances, there are problems, namely where there are still delays in handling disturbances, this is due to the length of time searching for the location of the disturbance. This paper aims to improve the handling of network disturbances using mobile devices. With a mobile device that is integrated with location base service, it can solve the problem of delay in handling network disturbances.